The relationship of thinking patterns associated with the two halves of the brain to the skills of handling and suppression in indoor soccer for female students of the College of Physical Education and Sports Sciences - Nahida Hamed Mashkoor; Intisar Ahmed Othman (دراسات وبحوث التربية الرياضية)
The aim of the research was to identify the learning and thinking patterns of the two halves of the brain among first-year female students in the College of Physical Education and Sports Sciences. The researchers used the descriptive approach using the correlational method, due to its suitability to the nature of the research problem, as the sample of the research was first-year female students in the College of Physical Education and Sports Sciences - University of Basra. The researchers relied on building a scale of the two halves of the brain as well as several tests. The researchers concluded that the diagnostic scale of learning and thinking patterns associated with the two halves of the brain showed the dominance of the left pattern of thinking, followed by the right pattern. They also recommended organizing and diversifying educational content and teaching methods in a way that develops the characteristics of the two halves of the brain together, which contributes to improving the ability to perform skills well.